Mitogen and stress activated kinases act co-operatively with CREB during the induction of human cytomegalovirus immediate-early gene expression from latency. - Verity G Kew; Jinxiang Yuan; Jeffery Meier; Matthew B Reeves (PLoS Pathogens)
The devastating clinical consequences associated with human cytomegalovirus (HCMV) infection and reactivation underscores the importance of understanding triggers of HCMV reactivation in dendritic cells (DC). Here we show that ERK-mediated reactivation is dependent on the mitogen and stress activated kinase (MSK) family. Furthermore, this MSK mediated response is dependent on CREB binding to the viral major immediate early promoter (MIEP). Specifically, CREB binding to the MIEP provides the target for MSK recruitment. Importantly, MSK mediated phosphorylation of histone H3 is required to promote histone de-methylation and the subsequent exit of HCMV from latency. Taken together, these data suggest that CREB binding to the MIEP is necessary for the recruitment of the kinase activity of MSKs to initiate the chromatin remodelling at the MIEP required for reactivation. Thus the importance of CREB during HCMV reactivation is to promote chromatin modifications conducive for viral gene expression as well as acting as a classical transcription factor. Clearly, specific inhibition of this interaction between CREB and MSKs could provide a strategy for therapeutic intervention.